2014
DOI: 10.12681/mms.547
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting recruitment seasonality of sea urchin species in Gran Canaria, Canary Islands (eastern Atlantic)

Abstract: Although sea-urchins can play an important role affecting the community structure of subtidal bottoms, factors controlling the dynamics of sea-urchin populations are still poorly understood. We assessed the seasonal variation in recruitment of three sea-urchin species (Diadema africanum, Paracentrotus lividus and Arbacia lixula) at Gran Canaria Island (eastern Atlantic) via monthly deployment of artificial collectors throughout an entire annual cycle on each of four adjacent habitat patches (seagrasses, sandy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…This implies that most A. lixula post-larvae settled on the collectors during the last two weeks of the sampling period (February 2012). These findings suggest that P. lividus and A. lixula do not entirely overlap their settlement peaks in the Canary Islands, as suggested by García-Sanz et al (2014), and that smallscale variations in settlement timing of these species may occur. The lack of A. lixula settlers in Tossa de Mar during the sampling period proves that the settlement timings of the two species studied are far from being synchronized in the Mediterranean Sea, unlike in the Canary Islands.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…This implies that most A. lixula post-larvae settled on the collectors during the last two weeks of the sampling period (February 2012). These findings suggest that P. lividus and A. lixula do not entirely overlap their settlement peaks in the Canary Islands, as suggested by García-Sanz et al (2014), and that smallscale variations in settlement timing of these species may occur. The lack of A. lixula settlers in Tossa de Mar during the sampling period proves that the settlement timings of the two species studied are far from being synchronized in the Mediterranean Sea, unlike in the Canary Islands.…”
Section: Discussionmentioning
confidence: 54%
“…Despite its ecological importance (Bulleri et al 1999, Guidetti et al 2003, Privitera et al 2011), settlement and recruitment stages of the black sea urchin have only been studied in the Canary Islands (Hernández et al 2005, García-Sanz et al 2014, probably because the occurrence of its settlers in the northwestern Mediterranean basin is inconspicuous and may be easily overlooked (Wangensteen 2013a). Unfortunately, our artificial collectors deployed in Mediterranean waters could not collect any A. lixula post-larvae during the study period (June 2012), so their efficiency could be only tested at Tenerife Island.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pedrotti and Fenaux (1992) reported a major peak of planktonic larval abundance of this species during October and November in the Ligurian Sea. García-Sanz et al (2014) showed one main recruitment peak in late winter-early spring (February, March, and April) for A. lixula in Gran Canaria Island. This recruitment peak coincides with the lower temperatures observed during the year (<18 C) and the period of maximum primary production in the study area.…”
Section: Larval Dynamics and Recruitmentmentioning
confidence: 95%
“…There are many factors involved in the regulation of the structure of urchin population; where predation, recruitment, pollution, diseases, large-scale oceanographic events, food supplies, niche variability are some of them (Hyman, 1955; Dayton et al , 1984; Hughes, 1994; Sala & Zabala, 1996; Sala & Ballesteros, 1997; 2007; Lessios, 2013; García-Sanz et al. , 2014). Hence, the ecological processes triggering these population explosions cannot be easily determined (Lessios et al (2001); Hernández et al , 2008; Lessios, 2013).…”
Section: Introductionmentioning
confidence: 99%